EVALUASI PENGHITUNGAN, PENYETORAN & PELAPORAN PPH PASAL 21 PADA PT. ASIA SAHABAT INDONESIA - Yulianto, Kampono Imam (Jurnal Akuntansi Dan Bisnis Indonesia (JABISI), 2021)
The purpose of this research is to know whether the counting, depositing, reporting of Tax pph artikel 21 (PPh article 21) employees of PT. Asia Sahabat Indonesia Period 2016 have in accordance with the regulation of minister director general taxes number PER-16/PJ/2016. This type of research is qualitative, the data collection techniques are by the study of documentaries, libraries and access websites and related sites. Data processing techniques by using Microsoft Office Word and Microsoft Excel. Data analysis techniques in this research by comparing and evaluating the counting, depositing, and reporting of pph artikel 21 against the regulation Director general taxes number PER-16/PJ/2016. From the research results obtained, the calculation, reporting and reporting of PPh Article 21 is not in accordance with the Regulation of the Director General of Taxes Number PER-31 / PJ / 2012